1972
DOI: 10.1002/oms.1210061013
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectral studies of unsaturated carboxylic acids—I: Some cyclic and acyclic βγ‐unsaturated acids

Abstract: The mass spectra of a series of &unsaturated cyclic and acyclic carboxylic acids are reported. Metastable ion studies and precise mass measurements have been employed in demonstrating that the ten compounds studied conform to one or other of two generalised fragmentation pathways.MASS spectral studies of carboxylic acids by electron-impact are relatively few, since they are more conveniently handled as the derived esters. Consequently the fragmentation behaviour of By-unsaturated acids has not been reported. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1976
1976
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The crude product was purified by flash column chromatography over silica eluting with 15% methanol/85% ethyl acetate to yield 9 as a viscous foaming liquid (61 mg, 80%). 1 80,81 1-(Benzyloxy)-N-( (10). The protected backbone 5 (200 mg, 0.410 mmol) was dissolved in TFA (5 mL) and CH 2 Cl 2 (5 mL).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The crude product was purified by flash column chromatography over silica eluting with 15% methanol/85% ethyl acetate to yield 9 as a viscous foaming liquid (61 mg, 80%). 1 80,81 1-(Benzyloxy)-N-( (10). The protected backbone 5 (200 mg, 0.410 mmol) was dissolved in TFA (5 mL) and CH 2 Cl 2 (5 mL).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…3-Butenoic acid (4) displays an appreciably different spectrum; loss of CO assumes greater importance and losses of H 2 0 , OH' and CH3' are relatively much less than in acids 1-3. The cyclic isomer (5) produces a characteristic intense [M -HI' peak, but the presence of prominent ions at mlz 71, 69, 68 and 58 show that this acid has features in common with its four isomers. As with the crotonic acids, mlz 45 is a doublet, [COOH]' and [&H,O]'.…”
Section: Normal Mass Spectra and Heats Of Formation Of The Molecular mentioning
confidence: 99%
“…The results indicated that dehydration (−18) occurred easily in seco -sativenes with strong abundance of dehydration peak observed in 1 - 8 , and similar reports were found in other studies ( McLafferty and Gohike, 1959 ; Alén, 1987 ; Nawamaki and Kuroyanagi, 1996 ; Sun et al, 2012 ; Giri et al, 2017 ; Qian et al, 2018 ). This may be due to an electron impact inducing fragmentations of alkene monocarboxylic acids to form an active OH ion, which combines an available methyl-hydrogen atom to one lost molecule of H 2 O (−18) through the McLafferty rearrangement in a six-membered system ( Baldas et al, 1969 ; Alexander et al, 1972 ). The molecular ion peak [M+H] + of 1 – 7 and 9 was not easily observed in the UPLC-Q-TOF-MS/MS profile, whereas [M+Na] + and [M+H-H 2 O] + abundances of these compounds were relatively strong.…”
Section: Discussionmentioning
confidence: 99%